(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article deals with the main and secondary normative legislative instruments providing the regulation process in gas distribution networks (TMG). The peculiarities of the legislation concerning the interaction of the supplier and consumer of natural gas with regard to the conclusion of contracts on transportation and distribution of gas as well as the provision of supply services and their payment. It analyzes the volumes of consumption, quality of received gas, ensuring a high level of consumers’ rights and interests protection, liability of the parties etc. The practical necessity of a clear regulatory framework functioning, which is the key to making the right decisions, avoiding controversial issues between suppliers and consumers of natural gas, improving the efficiency of business entities are determined. It describes the main provisions of the Law of Ukraine “On the Natural Gas Market”, the codes of gas transportation and gas distribution systems, the standard contracts for the supply and distribution of gas adopted in 2015 and reveals the key objectives and functions, the powers and procedure for their implementation of the National Commission carrying out state regulation in the fields of energy and utilities. Thus the very principled position of the National Commission which is a state regulator in the energy and utilities sectors will ensure equal rights for all participants of the gas market and as a result will enable the formation of a competitive market on which the consumer will play a major role. Such a position of supplier companies competing for the consumer will lead to positive changes such as lower prices and service improvement. In general the paper substantiates the need for changes and improvements in legislation to allow the formation of a competitive gas market to reach the level of European countries.